2017
DOI: 10.18517/ijaseit.7.2.2339
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Fatty Acid Profile of Fish Oil from Head of Tuna (Thunnus albacares) Extracted from Various Extraction Method

Abstract: By-product of tuna fish processing industry has the potential to be developed into fish oil rich in omega. Fish by-products are the main natural source of omega-3 polyunsaturated fatty acids, EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) with a great importance in food industry and pharmacy. The purpose of this research is to see the effect of fish oil extracting method from the head of tuna fish as by-product of tuna fish processing industry to the physicochemical properties and the profile of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
8
27
0
1
Order By: Relevance
“…Samples with a longer delay time for freezing present the highest mean levels (1.9 mg malondialdehyde/kg oil). The mean values of TBA content of extracted oil were considerably higher than those values reported in fish fillet by Abedi, Naseri, Ghanbarian, and Vazirzadeh, () and Tavakoli et al (); meanwhile, they are similar to those reported by Nazir et al () for tuna waste oils obtained using various extraction methods. Increasing TBA values during storage time are also reported in the oil extracted from Caspian white fish ( Rutilus frisii kutum ) and Nile perch ( Lates niloticus ) when freezing delay time becomes longer (Karungi et al, ).…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…Samples with a longer delay time for freezing present the highest mean levels (1.9 mg malondialdehyde/kg oil). The mean values of TBA content of extracted oil were considerably higher than those values reported in fish fillet by Abedi, Naseri, Ghanbarian, and Vazirzadeh, () and Tavakoli et al (); meanwhile, they are similar to those reported by Nazir et al () for tuna waste oils obtained using various extraction methods. Increasing TBA values during storage time are also reported in the oil extracted from Caspian white fish ( Rutilus frisii kutum ) and Nile perch ( Lates niloticus ) when freezing delay time becomes longer (Karungi et al, ).…”
Section: Resultssupporting
confidence: 62%
“…However, except for control group sample, alternations in SV of stored blanched samples (all treatments) were not statistically significant ( p > .05). Similarly, improved quality of final products via eliminating or inhibiting enzymatic activity using blanching treatment is reported by others (Ghaly et al, ; Nazir et al, ; Omodara & Olaniyan, ).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations